NEW VISION OF THE RELATIONSHIP OF THE STRUCTURE, FINITE PHYSICO-MECHANICAL PROPERTIES AND STRAIN BEHAVIOR OF NANO-STRUCTURED POLYMER SYSTEMS BASED ON OLIGODIISOCYANATES - Tereshatov, V.V.; Makarova, M.A.; Slobodinyuk, A.I.; Vnutskikh, Zh.A.; Senichev, V.Yu (Perm Federal Research Centre Journal, 2017)
The behavior of a nano-heterogeneous urethane-containing elastomer (UCE) was studied for the first time in the evolution of its structure. It was shown that the best strength properties of a UCE in awide range of strain rates were attained at the initial stage of the microphase separation of soft and hard blocks. There were different types of dependences of the material strength on the strain rate: positive, negative and an extreme one. Methods for effective regulation of the finite physical and mechanical properties of the UCE were proposed and implemented. New views on the hardening mechanism in urethane-containing polymers were substantiated. The relationships between the structure and the rate dependence of the strength characteristics for this type of elastomers were established. A number of materials with high strength and strain properties were developed.